Evaluasi Program "Karepe Dimesemi Bojo" Bagi Penyandang Disabilitas Mental Di Dinas Sosial Kabupaten Jombang - Aisyah Vira Ratnaningsih; Ertien Rining Nawangsari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
ABSTRACT. The Karepe Dimesemi Bojo (Independent Prosperous Mental Disability Rehabilitation Area of Jombang Regency) program is one of the innovations of the Jombang Regency Social Service which successfully became a finalist of the 2019 KOVABLIK. The Karepe Dimesemi Bojo program refers to poverty alleviation with the aim of increasing the role of people with mental disabilities in all areas of Jombang Regency in productive activities. This article aims to analyze the Evaluation of the Karepe Dimesemi Bojo Program for Persons with Mental Disabilities at the Jombang Regency Social Service. The theory used is the evaluation theory from William N Dunn (2003), which consists of Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. Data analysis uses analysis techniques from Miles, Hubernman and Salda (2014). The informants in the study included key informants, including the Head of the Social Rehabilitation Division and Mental Nurses, while secondary informants from the families of patients with mental disabilities who participated in the Karepe Dimesemi Bojo program. The results showed that the effectiveness and equity factors are not optimal because there are no independent shelters for people with mental disabilities. The adequacy factor is insufficient because the grant is still found to be a failure so that it needs to be re-evaluated. However, the efficiency, responsiveness, and accuracy factors show good results. Keywords: Evaluation; Karepe Dimesemi Bojo program ABSTRAK. Program Karepe Dimesemi Bojo (Kawasan Rehabilitasi Penyandang Disabilitas Mental Sejahtera Mandiri Kabupaten Jombang) merupakan salah satu inovasi Dinas Sosial Kabupaten Jombang yang berhasil menjadi finalis dari KOVABLIK tahun 2019. Program Karepe Dimesemi Bojo merujuk pada pengentasan kemiskinan dengan tujuan untuk meningkatkan peran masyarakat disabilitas mental di seluruh wilayah Kabupaten Jombang dalam aktivitas produktif. Artikel ini bertujuan untuk mengetahui Evaluasi Program Karepe Dimesemi Bojo Bagi Penyandang Disabilitas Mental Di Dinas Sosial Kabupaten Jombang. Artikel ini bertujuan untuk mengetahui Evaluasi Program Karepe Dimesemi Bojo Bagi Penyandang Disabilitas Mental Di Dinas Sosial Kabupaten Jombang. Teori yang digunakan adalah teori evaluasi dari William N Dunn (2003), yaitu Efektivitas, Efisiensi, Kecukupan, Perataan, Responsivitas, dan Ketepatan. Analisis data menggunakan teknik analisis milik Miles, Hubernman dan Salda (2014). Adapun informan pada penelitian meliputi informan kunci yaitu Kepala Bidang Rehabilitasi Sosial dan Perawat Jiwa, sedangkan informan tambahan dari keluarga pasien peyandang disabilitas mental yang mengikuti program Karepe Dimesemi Bojo. Hasil penelitian menunjukkan pada faktor efektivitas dan perataan belum optimal hal ini karena belum terdapat shelter mandiri bagi penyandang disabilitas mental. Pada faktor kecukupan dikatakan belum cukup karena bantuan yang diberikan masih ditemukan kegagalan sehingga perlu dilakukan evaluasi kembali. Namun, pada faktor efisiensi, responsivitas, dan ketepatan menunjukkan hasil yang baik. Kata kunci: Evaluasi; Program Karepe Dimesemi Bojo